Ethnic entrepreneurship: A qualitative study on entrepreneurial tendency of Meskhetian Turks living in the USA in the context of the interactive model - Sibel Ozafsarlioglu (Economics: The Open-Access, Open-Assessment Journal, 2024)
Ethnic entrepreneurship is the phenomenon that individuals from certain ethnic backgrounds participate in entrepreneurial activities. Individuals from those ethnic backgrounds are affected by various factors such as entrepreneurial tendencies, cultural values, social networks, and economic opportunities. Although such factors have the potential to explain ethnic entrepreneurship, it is important to continually update research and definitions in this field as ethnic entrepreneurship is an ever-growing topic. The purpose of this article is to be a part of the studies on ethnic entrepreneurship and to contribute to the field by identifying the conditions that influence the entrepreneurial process of Meskhetian Turks, who immigrated to the USA under special laws and became successful in establishing their own businesses. In order to achieve this purpose, in-depth interviews were conducted with entrepreneurs, and the findings are discussed in the context of the interactional model. According to the findings, social, capital, and ethnic networks play a significant role in business establishment and development, knowledge acquisition for business, and labor supply. In addition, due to the differences in the migration experiences of entrepreneurs, it is seen that both ethnic and non-ethnic networks affect entrepreneurship in the dimension of resource mobility. This study confirms the need to evaluate the benefits of ethnic entrepreneurship as a dynamic field.
Keywords: 330; ethnic entrepreneurship; interactional model; ethnic networks; non-ethnic networks; Meskhetian Turks